A dictionary of zoology - Allaby, Michael (Oxford University Press, 2003)
Dictionary of Zoology is a comprehensive and up-to-date reference work on all aspects of the study of animals. Containing over 5,000 entries on everything from animal behavior, ecology, and physiology to genetics, cytology, and evolution, the dictionary offers full taxonomic coverage of arthropods, fish, reptiles, amphibians, birds, and mammals. It is illustrated with clear line drawings, and supported by useful appendices on the genetic code, endangered animals, and SI units. Completely revised to incorporate the discovery of "extremophiles"--organisms living in environments formerly considered impossibly hostile--and the toxonomic reclassification that this has entailed, Dictionary of Zoology is ideal for students and will be invaluable to amateur naturalists and all those with an interest in zoology